The Invisibles in IB: How State agents’ export promotion support, finance, and time influence firms’ internationalization - Bitsch, Marion S. (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2024)
LOI. This thesis joins the conversation about the internationalization of the firm: Dunning’s Eclectic Paradigm (Ownership, Location, Internalization) operates as an envelope to anchor important factors that have previously received little attention in the IB conversation. These missing elements are the role of finance in explaining internationalization, the role of State agents, i.e. ECAs, and the role of time. The reason why it is important to deal with these omissions is because, many firms rely on export credit agencies’ (ECAs’) services to conduct either their early internationalization, or they rely on ECAs to provide financing tools to enable their later international business activities. This factor has surprisingly been neglected in most IB explanations on internationalization and the success and failure of MNEs. Within the thesis, I studied these in three separate studies. Essay 1, 2 and 3, have been conducted to shed light on the role of ECAs in firms’ internationalization. The three studies brought up surprising observations that were not sufficiently considered in the explanations of internationalization and how MNE safeguard their business. I focused on novel elements and applied an abductive reasoning (Saetre & Van de Ven, 2021). The surprising results in each of the studies, let me to search for a theoretical anchoring framework. I used Dunning’s OLI as an envelope to integrate the most important factors. These enhance our understanding of internationalization. Then I propose a new direction for the three dimensions conceptual model, presented as LOI. Regarding the contributions, I found as the results that the focused factors, finance, state agents and time, increase our understanding how ECAs support firms’ capabilities and influence how firms make their internationalization decisions. And I am highlighting new factors that increase the explanatory power of the internationalization journey of firms: capabilities, willingness and the goal. The research contributes to academia beyond IB through the methodology used. The abductive reasoning serves as a concrete illustration of how a human brain conceives and constructs internationalization decision making. The dimension that connects it to natural Life sciences and biological models, is the innovation of this thesis: the concept of time internalization.

---- LOI. Tämän väitöskirjan kontribuutio kohdistuu teoretisointiin näkymättömien tekijöiden roolista yritysten kansainvälisessä liiketoiminnassa. Väitöskirja tutkii, miten viennin edistäminen, rahoitus ja aika yhdessä selittävät yritysten kansainvälistymistä. Tätä kysymystä pohditaan rationaalisen abduktion (Saetre & Van de Ven, 2021) avulla. Väitöskirjassa peilataan useiden sidosryhmien näkökulmia ja työn käsitteel-linen positio rakentuu Dunningin eklektisen paradigman ympärille. Tämä malli yhdistää omistajuuden sijaintiin liittyviin etuihin ja sisäisen hallinnan eri tyyppeihin. Tämän OLI (Ownership, Location, Internalization) -viitekehyksen sisällä tässä työssä keskitytään sijainnin eli lokaation alakohtana viennin edistämiseen, omistajuuden alakohtana rahoitukseen ja sisäisen hallinnan alakohtana ajan rooliin. Nämä tekijät ovat toisiinsa kytkeytyneitä kansainvälisissä vaihtotransaktioissa ostajien ja myyjien välillä. Vaihdon juurtuneisuus kuvaa OLI-osatekijöiden näky-mättömyyttä kansainvälisessä liiketoiminnassa. Tämä väitöskirja jakautuu neljään osaan. Ensimmäisessä esitellään yhteenveto viennin edistämiseen liittyvästä tiedosta ja määritelmistä, sekä kartoitetaan olemassa olevat viennin edistämiseen liittyvät teoriat. Toisessa osassa arvioidaan rahoitusta omistajuuteen liittyvänä tekijänä ja yrityksen ikää omistajuuteen liittyvänä etuna yritysten kansainvälistymistä edistävinä tai sitä rajoittavina tekijöinä. Kolmantena esitellään kyselytutkimuksen tuloksia viennin edistämistoimenpiteiden suhteesta yritysten kansainvälistymisen ajoitukseen. Viimeisenä keskustellaan löydösten vertailevasta analyysistä ja ehdotetaan yritysten kansainvälistymisen tukemisen strategiaa sekä vienninedistäjille että rahoittajille perustuen saatuun syvempään ymmärrykseen asiakasyritysten tavoitteista halukkuuden näkökulmasta, pelkän kyvykkyyden lisäksi. Tämä tutkimus täydentää Dunningin alkuperäistä mallia paljastamalla vähem-mälle huomiolle jääneet tekijät OLI-viitekehyksen saumakohdissa. Viitekehykseen lisätään ajan dynaamisuus sisäisen hallinnan dimensiona ja toimintahalukkuuden vaikutin, jonka rooli ajan sisäistämisessä on kriittinen. Lisäksi tutkimus selittää, miksi on tärkeää erottaa toisistaan yrityksen toimintahalukkuus ja toiminta-kyvykkyys, sillä halukkuus on kytköksissä yrityksen tehokkuuteen ja strategiaan. Tämä tutkimus ehdottaa, että erilaiset implisiittiset oletukset ajasta mahdollisesti heikentävät yrityksen toimien koordinoimista paikkaan liittyen erityisesti pitkien matkojen välillä, digitaalisissa suhteissa ja valtiorajojen yli. Lopullinen käsitteel-linen viitekehys esittää yhden ratkaisun toimivan kansainvälistymisstrategian tunnistamiseen: omistajuuden ja ajan synkronoinnin sisäistämisen kautta, mukaan lukien kyvyn ja halukkuuden saavuttaa määritelty kansainvälistymistavoite.